EFFECT OF COOPERATION WITH THE EUROPEAN AGENCY FOR THE MANAGEMENT OF OPERATIONAL COOPERATION AT THE EXTERNAL BORDERS OF THE MEMBER STATES OF THE EUROPEAN UNION (FRONTEX) ON THE FACILITATION OF TRAINING PROCESS OF THE LATVIAN STATE BO - Arbidāne, Iluta; Lobanovs, Aleksejs; Pokule, Viktorija; Liepiņš, Arvīds (Border Security and Management, 2016)
The research focuses on major cooperation directions established between the State Border Guard of Latvia and the European Agency FRONTEX. It deals with the legal regulation of SBG and FRONTEX cooperation, depicts and analyses SBG and FRONTEX cooperation in the field of training as well as explores the main pillars of SBG and FRONTEX cooperation development perspectives. The aim of the research is to investigate how SBG cooperation with the Agency for the Management of Operational Cooperation at the External Borders of the Member States of the European Union (Frontex) influences the increase of SBG officers’ capacity regarded in carrying out their functions. The main tasks that were brought up are as follows: to investigate the legal regulation of SBG and FRONTEX cooperation as well as to analyse the main directions of SBG and FRONTEX cooperation in the training process of the officers, finally, to study perspectives of SBG and FRONTEX cooperation development aiming at officers’ capacity building.  The key methods employed in the framework of this research are: descriptive method, analysis and synthesis, clustering, graphical method.